Transdermal absorption enhancement of papain loaded in elastic niosomes incorporated in gel for scar treatment - Manosroi A. (2014)
Papain is one of the protease enzymes from Carica papaya latex which is widely used in dermatology for scar treatment. The aim of this study was to compare the penetration of papain from gel formulations containing niosomes and nanospheres loaded with papain. The vesicular sizes of all niosomes and nanospheres in the gel formulations were in the range of 220.7-520.2 nm. Papain loaded in elastic niosomes and incorporated in gel exhibited the accumulate amounts and fluxes of 0.226 mg/cm2 and 0.029 mg/ cm2/h in the whole rat skin and 0.220 mg/cm2 and 0.037 mg/cm2/h in the receiving solution, which were 3.10, 2.38 and 2.24, 2.25; 10.08, 7.78 and 4.92, 4.93; 4.86, 3.71 and 7.38, 7.38 times more than that from gel containing papain loaded in non-elastic niosomes, PLGA nanospheres and in solution, respectively, investigated by Franz diffusion cells at 6 h. All gel formulations incorporated with papain loaded in niosomes and nanospheres gave no irritation on rabbit skin. Gel containing papain loaded in elastic niosomes gave superior chemical stability to gel containing free papain of 1.13, 1.29 and 1.35 times when stored at 4 ± 2, 27 ± 2 and 45 ± 2 C after 3 months, respectively. After 28 days of application, gel containing papain loaded in elastic niosomes (GEN) exhibited higher reduction of hypertrophic scars of the induced scar on rabbits' ears determined by a vernier caliper than gel base (GB), gel containing free papain (GS), and gel containing papain loaded in non-elastic niosomes (GNN) of 10.20, 2.73 and 2.31 times, respectively. For histological examination, the numbers of collagen fibres and the height of the scars treated with GEN were significantly decreased compared with the control group. This study has demonstrated the potential of niosomes, especially the elastic niosomes, for the enhancement of rat skin transdermal absorption of papain and the improvement of scar reduction in rabbit ear model which will be beneficial for the development of topical products for scar treatment. Crown Copyright © 2012 Published by Elsevier B.V. All rights reserved.